How to Pay your Students to Go to School: Student-run record labels and the creative pedagogue - Lipset, Michael (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2020)
The author examines a federally funded internship program he organized while serving as the director of the High School for Recording Arts Los Angeles program. The school paid students to operate their own record label. Under the American Workforce Innovation and Opportunity Act, approved organizations provide paid, for-credit internships to young people who meet the definition of opportunity youth. Through this partnership, students learned real-world skills, gained hands-on experience, and built their resumes. The author experienced a shift in his professional praxis from school leader to creative pedagogue. During the internship, the school experienced increased student attendance and enrolment, suggesting the paid internship resulted in increased opportunities for student learning. The author covers similar opportunities across the US and Canada.